(untitled) (Journal of Ideas in Health, 2024)
Background: Over the past two decades, laparoscopic surgeries have significantly progressed, and surpassing traditional surgical methods across multiple medical fields. This study aims to assess the patients’ satisfaction and the related factors toward the laparoscopic cholecystectomy in Iraq. Methods: A cross-sectional study was conducted from April 2023 to 30th March 2024 at the Alkalis General Hospital and Al Hayat Private Hospital, Diyala province, Iraq. Semi-structured questionnaire was recruited to collect the pre and post operative data from patients. Statistical analysis was carried out using SPSS-21, with significance set at p < 0.05. Results: Data of 157 patients with mean age (+ Standard Deviation) of 47.57 (SD +12.80) were analyzed. Most of them (53.5%) were females, operated in public hospitals (52.2%), unemployed (51.6%), and earned less than USD 400 (60.5%). The majority of patients expressed high overall satisfaction with the laparoscopic cholecystectomy procedure (42.7% being strongly satisfied and 38.9% satisfied). In the multiple logistic regression, the patients who were operated in private hospital (OR = 4.506, 95% CI: 1.394 to 14-577; P-value= 0.012), with monthly income exceeds USD 400 (OR = 4.887, 95% CI: 1.531 to 15.601; P-value=0.007), involved in the choosing of surgery technique (OR = 5.596, 95% CI: 1.425 to 21.982; P-value=0.014), and those recommend laparoscopic cholecystectomy for others (OR = 9.100, 95% CI: 1.425 to 21.982; P-value=0.001), had the highest odds ratios. The Hosmer and Lemeshow test indicated a good fit (p = 0.552). Conclusion: Patient satisfaction is high especially among high income patients operated in private hospital however, the perception of postoperative outcomes remains important areas of focus, particularly in regions with unique healthcare challenges like Iraq.